2021
DOI: 10.3389/fimmu.2020.628576
|View full text |Cite
|
Sign up to set email alerts
|

Immunoregulatory Effects of Mitochondria Transferred by Extracellular Vesicles

Abstract: Mitochondria participate in immune regulation through various mechanisms, such as changes in the mitochondrial dynamics, as metabolic mediators of the tricarboxylic acid cycle, by the production of reactive oxygen species, and mitochondrial DNA damage, among others. In recent years, studies have shown that extracellular vesicles are widely involved in intercellular communication and exert important effects on immune regulation. Recently, the immunoregulatory effects of mitochondria from extracellular vesicles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 74 publications
0
14
0
Order By: Relevance
“…This secreted material includes EVs, lipid bilayer-delimited vesicles that carry proteins, DNA and RNA molecules. As such, EVs have been implicated in a large range of physiological and pathological processes, including immune responses, cancer progression, and neurodegeneration ( Shanmughapriya et al, 2020 ; Ma et al, 2021 ; She et al, 2021 ). EVs can be divided into different types based on their size and origin: exosomes are 30–150 nm in size and derived from intracellular vesicles (multivesicular bodies, a form of late endosome); microvesicles directly bud off the plasma membrane and are usually between 100 and 1000 nm; while apoptotic bodies are generated from dying cells and are generally between 100 and 5000 nm ( Devhare and Ray, 2018 ; Théry et al, 2018 ).…”
Section: Extracellular Vesiclesmentioning
confidence: 99%
“…This secreted material includes EVs, lipid bilayer-delimited vesicles that carry proteins, DNA and RNA molecules. As such, EVs have been implicated in a large range of physiological and pathological processes, including immune responses, cancer progression, and neurodegeneration ( Shanmughapriya et al, 2020 ; Ma et al, 2021 ; She et al, 2021 ). EVs can be divided into different types based on their size and origin: exosomes are 30–150 nm in size and derived from intracellular vesicles (multivesicular bodies, a form of late endosome); microvesicles directly bud off the plasma membrane and are usually between 100 and 1000 nm; while apoptotic bodies are generated from dying cells and are generally between 100 and 5000 nm ( Devhare and Ray, 2018 ; Théry et al, 2018 ).…”
Section: Extracellular Vesiclesmentioning
confidence: 99%
“…Potential TEV-mediated immune suppression mechanisms involving the reprogramming of immune cell mitochondria include (i) modulating metabolism to inactivate their tumor suppressor function and (ii) triggering mitochondria mediated apoptosis (Figure 3B). Interestingly, immunoregulatory effects can also be induced by the transfer of whole mitochondria via EVs [170].…”
Section: Avoiding Immune Destructionmentioning
confidence: 99%
“…In the first case, changes in allelic frequencies occur through the mitochondria random distribution during mitosis; in the second case, present in post-mitotic cells or non-dividing cells, heteroplasmy depends on the mtDNA replication rate and other cellular processes such as mitochondrial fusion and fission, as well as mtDNA transference between cells ( Figure 1 ) [ 49 , 57 ]. Thus, heteroplasmy is an extraordinarily complex and dynamic event that results from various stochastic and deterministic cellular processes [ 18 , 62 , 63 , 64 , 65 , 66 ]. Human pedigree analysis has shown that random genetic drift is involved in heteroplasmy and in combination with mitochondrial segregation, and the horizontal transfer of cell–cell mitochondria, modifies the allele frequencies of mtDNA over time.…”
Section: Origins Of Heteroplasmy and Its Impact On Diseasementioning
confidence: 99%